Maternal Exposure to Herpes Simplex Virus and Risk of Psychosis Among Adult Offspring - Buka, Stephen L.; Cannon, Tyrone D.; Torrey, E. Fuller; Yolken, Robert H. (Biological psychiatry (1969), 2008)
Viral exposure during gestation is thought to be a risk factor for schizophrenia. Previous studies have indicated that prenatal exposure to herpes simplex virus type 2 (HSV-2) may be a risk for the subsequent development of schizophrenia in some populations. In this investigation, we tested a large and diverse population to assess the risk of psychoses among offspring of mothers with serological evidence of HSV-2 infection. We conducted a nested case-control study of 200 adults with psychoses and 554 matched control subjects (matched for city and date of birth, race/ethnicity, gender, and parent history of treatment for mental disorder) from three cohorts of the Collaborative Perinatal Project (Boston, Providence, and Philadelphia). We analyzed stored serum samples that had been obtained from these mothers at the end of pregnancy for antibodies directed at HSV-2, using type-specific solid-phase enzyme immunoassay techniques. Offspring of mothers with serologic evidence of HSV-2 infection were at significantly increased risk for the development of psychoses (odds ratio [OR] = 1.6; 95% confidence interval [CI] = 1.1–2.3). This risk was particularly elevated among women with high rates of sexual activity during pregnancy (OR = 2.6; 95% CI = 1.4–4.6). Maternal exposure to herpes simplex virus type 2 is associated with an increased risk for psychoses among adult offspring. These results are consistent with a general model of risk resulting from enhanced maternal immune activation during pregnancy.